The Relationship Between the Nutritional Status of Pregnant Women, Infant Birth Weight and Stunting Incidence in Toddlers - Johanna Christy; Esraida Simanjuntak (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Stunting is still a major nutritional problem faced by Indonesia. The prevalence of stunting in North Sumatra ranks nineteenth at 21.1%. Mandailing Natal District has the highest prevalence in North Sumatra Province at 47.7%. This study aimed to determine the relationship between the nutritional status of pregnant women (LILA) and the birth weight of infants aged 6-36 months with the stunting process in the Working Area of the Kotanopan Health Center, Mandailing Natal. This type of research is observational with a cross-sectional study design with a sample of all infants aged 6-36 months at the Kotanopan Health Center, Mandailing Natal. This research was conducted in the Working Area of the Kotanopan Health Center, Mandailing Natal, in December-February 2023. The population in this study was all toddlers aged 6-36 months, totaling 1457 toddlers. The sample in the study was 97 toddlers. They collected data in this study using a questionnaire. The sampling technique uses simple random sampling-data analysis in this study with the Chi-Square test. The results of the study explained that there were 97 respondents for the category of nutritional status of pregnant women (LILA), and 34.0% of pregnant women experienced chronic energy deficiency. There were 25.7% of babies born with low birth weight (LBW) and 47.4% of babies experiencing stunting for the category of infant nutritional status based on height/age. The results of statistical tests showed that there was a significant relationship between the Nutritional Status of Pregnant Women (LILA) and stunting in infants (p=0.01) and birth weight in infants with stunting (p=0.02). Suggestions for health workers need to increase the provision of PMT to pregnant women to prevent an increase in the number of pregnant women suffering from CED in the working area of the Kotanopan Health Center, Mandailing Natal. Keywords: Infant Birth Weight, Stunting, Upper Arm Circumference (LILA)